EVALUATION OF ANTIBACTERIAL ACTIVITY OF METAL NANOPARTICLES AGAINST DIFFERENT PATHOGENIC BACTERIA. (Global Journal of Advanced Engineering Technologies and Sciences, 2015)
In recent years, infectious diseases are increasingly being encountered in clinical settings. Due to the development of antibiotic resistance and the outbreak of these diseases caused by resistant pathogenic bacteria, the pharmaceutical companies and the researchers are now searching for new unconventional antibacterial agents. Recently, in this field, the application of nanoparticles is an emerging area of nanoscience and nanotechnology. For this reason, nanotechnology has a great deal of attention from the scientific community and may provide solutions to technological and environmental challenges. A common feature that these nanoparticles exhibit their antimicrobial behavior against pathogenic bacteria. In this report, we evaluate the antibacterial activity of Ag, Fe and ZnO nanoparticles against both Gram-negative (E. coli and P. aeruginosa) and Gram-positive (Staph. aureus) bacteria, using agar well diffusion method, as well as determine of minimal bactericidal concentrations by the broth dilution method. The results showed that antibacterial activities of these nanoparticles were found active against both Gram-positive and Gram-negative bacteria used in this study. Among the three nanoparticles, Ag nanoparticles have excellent bactericidal potential, while Fe nanoparticles exhibited the least bactericidal activity